A atividade social nas aulas de língua espanhola: uma relação dialética entre a vida do aluno e o processo de ensino‐aprendizagem - Rodrigues, Penélope Alberto (2012)
The purpose of this research is to get a critical understanding about the changes in the teaching and learning process through daily living activities in the classroom based on the Social Activity. This study, along with the Language in Activity in School Context research group (PUC‐SP), analyses how a social activity work in the Spanish classes contributes meaningfully to the students development. This research which was developed at a private school in the city of São Paulo, is measured on the Social‐ Cultural‐Historical Activity Theory, based on Vygotsky ideas (1934‐2008), who agrees that the knowledge must be taught and contextualized according to the individual needs; also based on Bakhtin (1979‐1997), who thought that the statement reflexes condition and use of each human activity field; on Leontiev (1977‐1997) and Engeström (1987‐1999) who defend that the human activity is a joint of stuck actions by a group to achieve a goal together as well. The investigation is introduced in the Applied Linguistic field for being a transdisciplinary study of the language in a specific school context. The work which was developed during the first term in 2011 with the 8th grade students is organized as a Critical Search for co‐operation (MAGALHÃES, 2006), allows that the every individual who is involved can take part into the knowledge construction, so they are able to create and recreate new possibilities of work. The produced data were collected through audio and visual recorded classes and examined according to the Dialogical‐enunciative perspective. The corpus analysis is organized through the linguistic materiality in the participants (students and teacherresearcher) speeches. The data interpretation has the key concept TASCH in relation to knowledge construction during social interactions and through the double movement between scientific and spontaneous concepts.The results show the importance in establishing a dialectical relation between the teaching and learning process and the student life to recognize and analyze and reflect about the developed contents into the classes and used in real situations of life